STRATEGI PENGELOLAAN LAHAN KRITIS - WIYONO, WIYONO (JURNAL ILMIAH AGRINECA, 1970)
Ready challenge of food progressively day progessively heavily.Degradation of Farm and envirenment , either by act of human being and alsonatural troble, progressively.